Modern Approaches to Strengthening Working Surfaces of Mill and Pump Components Against Wear - Sherzodjon Rakhimboev; Bekhzod Abdurafikov (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article examines modern combined technologies aimed at strengthening the working surfaces of mill and pump components and enhancing their resistance to intensive wear. It identifies the limitations of conventional surface-hardening methods and highlights the advantages and disadvantages of advanced techniques such as thermal-chemical treatment, ultrasonic surface modification, laser hardening, and electromagnetic-pulse strengthening. The study explores real-time monitoring possibilities based on digital sensors, laser scanning, ultrasonic diagnostics, and electromagnetic response measurements, which enable continuous control of wear intensity and surface condition. The high efficiency of combined technologies—such as laser + ultrasonic treatment or electromagnetic strengthening + surface alloying—is scientifically substantiated, and their role in improving surface integrity, microstructural uniformity, hardness distribution, and long-term operational durability is described. The article also presents prospects for process modeling using digital twins and adaptive control systems based on artificial intelligence to optimize strengthening parameters. It is concluded that the industrial implementation of improved combined technologies ensures significant energy savings, extended service life of components, enhanced reliability of mill and pump equipment, and overall improvement in economic performance.